IDH-Inhibitoren = IDH inhibitors - Krämer, Alwin; Heuser, Michael (Der Onkologe, 2017)
BackgroundSomatic mutations in isocitrate dehydrogenase (IDH) 1 and IDH2 have been identified in multiple human cancers, including glioma, chondrosarcoma, cholangiocellular carcinoma, angioimmunoblastic T cell lymphoma, myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML).ObjectiveThis review article summarizes the current data on the use of IDH inhibitors for tumors with IDH1 and 2 mutations. A description of the mutation diagnostics, which ultimately lead to a decision on therapy is also given.MethodsClinical data on the treatment of patients with mutation-specific IDH inhibitors are currently available for one IDH1 inhibitor and two IDH2 inhibitors for patients with AML and MDS as well as one IDH1 inhibitor for glioma patients.ResultsOverall response rates of AML and MDS patients to the different inhibitors are approximately 35-40%. Additionally, the majority of patients profit from an increase in the numbers of functionally active neutrophilic granulocytes, which is associated with a reduction in infection rates. The most frequent side effects are mild hyperbilirubinemia, elevated transaminase levels and nausea.ConclusionAs several studies with mutation-specific IDH1 and IDH2 inhibitors are currently recruiting, all patients with AML, MDS and gliomas should be tested for mutations in IDH1 and IDH2 and included in studies. In the future these studies will investigate not only monotherapy but also combination therapies with, e.g. azacitidine or intensive chemotherapy and include previously treated as well as newly diagnosed patients. Currently, IDH inhibitors represent an important new development in the treatment of AML and MDS patients.
Paralleltitel von Frontdoor übernommen
Gesehen am 07.11.2018